Information personalization for e-government service in Malaysia - Prima, Silviana (2010)
Government sector nowadays is trying to expand the use of Information and Communication Technology (ICT) to provide the services to citizen. Personalization is part of evolution of ICT in delivering the relevant information tailored to citizen’s needs and preferences. Personalization has been widely implemented in the private sector, but recently still gains the new concept in the government sector. Understand the needs of citizens are very important to improve the citizen satisfaction and result to repetitive visit. Based on the findings from another researcher, personalization is positively related to service quality. There are various personalization models have been reviewed by researcher, but an appropriate personalization models are selected based on the services provided by government. Beside that, the implementation of personalization in the private sector and oversea public sector need to be studied for personalization model benchmarking. To meet the best result from this project, Majlis Perbandaran Johor Baru Tengah (MPJBT) is researcher’s selected case study in order to achieve the objective of this project. Hopefully the result of this project will give a beneficial contribution for information delivery to its citizen.